A Case Study of Visually Impaired Student on A Learning Style and Learning Strategies in English Learning in Visually Impaired Charitable Institution Aisiyah Ponorogo - Yolanda Nadya Galerin; Niken Reti Indriastuti; Diyah Atiek Mustikawati (EDUPEDIA, 2021)
This research aimed to find out: (1) the difficulties that faced by Visually Impaired Students (2) the learning style that used by Visually Impaired Students (3) the learning strategiess that used by Visually Impaired Students. The type of research is descriptive qualitative research in the form of case study.. There are three visually impaired students, teacher, orphanage caregiver involved in this research. In this research, the researcher used observation, questionnaire and interview for instrument. Further the data analysis used Miles and Huberman model with the steps as following: data reduction, data display, and conclusion. The result shows that the difficulties appeared because there were in inclusive class. Almost of them felt difficult when the learning process was seeing the media such as presentation or watching a visual picture or videos. To overcome it they had different strategies.. The researcher classified that One students had memory strategies, compensation strategies and social strategies. One student used affective strategies. One student used metacognitive strategies. Based on the learning style, the most of visually impaired students were auditory learners. It can seen from all of Visually Impaired Students said that it more easier when listening to the teachers but if they didn’t understand they wrote the material first on the notebook. So, the Visually Impaired Student easier to understand the material that given by the teacher through listening. Visually Impaired Student at Charitable Institution ‘AisyiyahPonorogo didn’t have visual learning style because they were totally blind.